Perbandingan Administrasi Publik Indonesia dan Amerika Serikat dalam Struktur Birokrasi Desentralisasi dan Pelayanan Publik - Imam Haromain; Aminullah Aminullah (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2026)
This study aims to analyze and compare public administration systems in Indonesia and the United States, focusing on bureaucratic structure, decentralization mechanisms, and public service delivery. Using a qualitative approach through literature review, this research examines scholarly articles, policy documents, and relevant regulations published in recent years. The findings show that Indonesia adopts a hierarchical and relatively centralized bureaucratic structure within a decentralized unitary state framework, while the United States applies a federal system that grants constitutionally guaranteed autonomy to state governments. Decentralization in Indonesia emphasizes administrative and political authority transfer to local governments to improve service responsiveness, although challenges such as overlapping authority and uneven institutional capacity persist. In contrast, federalism in the United States enables flexible and innovative public service provision but also creates disparities among states. The study further reveals that public service effectiveness and responsiveness in both countries are influenced by bureaucratic capacity, coordination mechanisms, and digital governance implementation. This comparative analysis provides insights for policymakers to strengthen bureaucratic reform, improve intergovernmental coordination, and enhance public service quality in accordance with national governance contexts.